2023
DOI: 10.1111/trf.17485
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion reactions associated with COVID‐19 convalescent plasma in outpatient clinical trials

Abstract: BackgroundCOVID‐19 convalescent plasma (CCP) is an important therapeutic option for outpatients at high risk of hospitalization from SARS‐CoV‐2 infection. We assessed the safety of outpatient CCP transfusions administered during clinical trials.Study Design and MethodsWe analyzed data pertaining to transfusion‐related reactions from two randomized controlled trials in the U.S. that evaluated the efficacy of CCP versus control plasma in various ambulatory settings. Multivariable logistic regression was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Additional concerns were initially raised, such as antibody-dependent enhancement (ADE) of viral infection, and transfusion reactions. All those concerns have remained theoretical so far, and several systematic reviews and metanalyses have found no increased risk compared with transfusion of fresh frozen plasma [16]. An additional concern regards the occurrence of venous and arterial thrombotic adverse events related to CCP transfusion, an issue not so trivial considering the highly prothrombotic context of COVID-19 and the presence of procoagulant factors in fresh frozen plasma.…”
Section: Safety Of Ccpmentioning
confidence: 99%
“…Additional concerns were initially raised, such as antibody-dependent enhancement (ADE) of viral infection, and transfusion reactions. All those concerns have remained theoretical so far, and several systematic reviews and metanalyses have found no increased risk compared with transfusion of fresh frozen plasma [16]. An additional concern regards the occurrence of venous and arterial thrombotic adverse events related to CCP transfusion, an issue not so trivial considering the highly prothrombotic context of COVID-19 and the presence of procoagulant factors in fresh frozen plasma.…”
Section: Safety Of Ccpmentioning
confidence: 99%
“…Additional concerns were initially raised, such as antibody-dependent enhancement (ADE) of viral infection and transfusion reactions. All of those concerns have remained theoretical so far, and several systematic reviews and metanalysis have found no increased risk compared to transfusion of fresh frozen plasma [13,14]. An additional concern is the occurrence of venous and arterial thrombotic adverse events related to CCP transfusion, an issue not so trivial considering the highly prothrombotic context of COVID-19 and the presence of procoagulant factors in fresh frozen plasma [12].…”
Section: Safety Of Ccpmentioning
confidence: 99%
“…Additional concerns were initially raised, such as antibody-dependent enhancement (ADE) of viral infection, and transfusion reactions. All those concerns have remained theoretical so far, and several systematic reviews and metanalyses have found no increased risk compared to transfusion of fresh frozen plasma [20,21]. An additional concern regards the occurrence of venous and arterial thrombotic adverse events related to CCP transfusion, an issue not so trivial considering the highly prothrombotic context of COVID-19 and the presence of procoagulant factors in fresh frozen plasma [16].…”
Section: Safety Of Ccpmentioning
confidence: 99%